2016
DOI: 10.1038/srep36017
|View full text |Cite
|
Sign up to set email alerts
|

Circulating vitamin D in relation to cancer incidence and survival of the head and neck and oesophagus in the EPIC cohort

Abstract: Experimental and epidemiological data suggest that vitamin D play a role in pathogenesis and progression of cancer, but prospective data on head and neck cancer (HNC) and oesophagus cancer are limited. The European Prospective Investigation into Cancer and Nutrition (EPIC) study recruited 385,747 participants with blood samples between 1992 and 2000. This analysis includes 497 case-control pairs of the head and neck and oesophagus, as well as 443 additional controls. Circulating 25(OH)D3 were measured in pre-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 25 publications
3
56
1
Order By: Relevance
“…did demonstrate a protective role for 25OHD in ovarian cancer in a well powered MR study. Despite the body of evidence that does not support a protective effect of 25OHD on cancer incidence, there is evidence to support the hypothesis that vitamin D has an effect on cancer progression 8, 11…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…did demonstrate a protective role for 25OHD in ovarian cancer in a well powered MR study. Despite the body of evidence that does not support a protective effect of 25OHD on cancer incidence, there is evidence to support the hypothesis that vitamin D has an effect on cancer progression 8, 11…”
Section: Discussionmentioning
confidence: 99%
“…Despite the body of evidence that does not support a protective effect of 25OHD on cancer incidence, there is evidence to support the hypothesis that vitamin D has an effect on cancer progression. 8,11 The genetic instrument used in our study specifically proxies average total (free and bound) circulating 25OHD and does not necessarily predict the concentrations of free 25OHD available at the tissues or concentrations of free or bound 1,25OH 2 D in circulation or at the tissue level. Potential anti-cancer effects of vitamin D are via free 1,25OH 2 D interacting with the vitamin D receptor within tissues resulting in reduced angiogenesis, metastasis, cell invasion, inflammation, and proliferation as well as upregulation of apoptosis.…”
Section: Cancer Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Research into the impact of vitamin D with respect to oesophageal adenocarcinoma risk is highly controversial, with observational studies having reported null results, decreased risks, or indeed increased risks of oesophageal adenocarcinoma in patients with higher levels of vitamin D intake or status [ 21 24 ]. No clear associations for circulating vitamin D levels and prognosis after a diagnosis of oesophageal cancer were identified in a European cohort study, although that included only 74 adenocarcinoma patients [ 25 ]. Our study provides some evidence that VDR is associated with oesophageal adenocarcinoma outcomes, and therefore indirect evidence of a biological role for vitamin D.…”
Section: Discussionmentioning
confidence: 99%